PhytocPhytochemical Composition Of Ipomoea Batatas And Moringa Oleifera leaves and crackers from underutilised flours. hemical Composition Of Ipomoea Batatas And Moringa Oleifera Leaves And Crackers From Underutilised Flours. - Owusu, Deborah (2011)
A THESIS SUBMITTED TO THE DEPARTMENT OF BIOCHEMISTRY AND BIOTECHNOLOGY FACULTY OF BIOSCIENCES, COLLEGE OF SCIENCE, KWAME NKRUMAH UNIVERSITY OF SCIENCE AND TECHNOLOGY IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE AWARD OF MASTER OF SCIENCE (MSC) DEGREE,